2019
DOI: 10.1088/1757-899x/609/3/032027
|View full text |Cite
|
Sign up to set email alerts
|

The influence of urban microclimate vertical variations on the building performance of a high-rise office building at different floors

Abstract: This paper explores the urban microclimate effects on the building performance of high-rise office buildings of different heights. In general, the environment section of buildings’ performance calculation relies on weather station data located in rural areas which are quite different from the actual urban microclimate. How the accuracy of urban microclimate modelling affects the building performance simulation is not understood. We have previously explored horizontal elements’ effects on high-rise office build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The urban microclimate is one of the most critical factors affecting outdoor thermal comfort [33], the urban life quality [9][17] [24], the utilisation of the outdoor public spaces [33] [35] [36], and the liveability and sustainability of cities [14], [8], [37]. There are several thermal comfort indices developed, considering the relationship between microclimate and thermal sensation.…”
Section: Contribution Of the Urban Microclimate To Outdoor Thermal Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…The urban microclimate is one of the most critical factors affecting outdoor thermal comfort [33], the urban life quality [9][17] [24], the utilisation of the outdoor public spaces [33] [35] [36], and the liveability and sustainability of cities [14], [8], [37]. There are several thermal comfort indices developed, considering the relationship between microclimate and thermal sensation.…”
Section: Contribution Of the Urban Microclimate To Outdoor Thermal Co...mentioning
confidence: 99%
“…Jing et al [81], [82], [16] demonstrated that, when modelling the thermal performance of naturally ventilated buildings in dense urban areas, the model must account for: the effect of UHI within the urban canopy layer; the influence of the vertical structure of the wind within the urban boundary layer;…”
Section: A Critical Review Of Urban Microclimate Studies In Nzmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the causative factors is that the built-up areas are covered by building materials with higher heat absorption than the suburban or rural areas with a higher ratio of vegetation coverage or of water bodies [2,3]. Another factor that causes the UHI effect is the urban geometry formed by high-rise buildings that alter the air dynamics in between street canyons, which potentially prevents cool prevailing winds from entering the core of the city and limits natural ventilation for cooling [4]. Many studies have mentioned the potential risks that urban heat poses to human health and well-being, which can be fatal under extremely hot weather events [5,6].…”
Section: Introductionmentioning
confidence: 99%